2010
DOI: 10.1001/archpediatrics.2010.96
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Delaying School Start Time on Adolescent Sleep, Mood, and Behavior

Abstract: To examine the impact of a 30-minute delay in school start time on adolescents' sleep, mood, and behavior.Design: Participants completed the online retrospective Sleep Habits Survey before and after a change in school start time.Setting: An independent high school in Rhode Island.Participants: Students (n=201) in grades 9 through 12.Intervention: Institution of a delay in school start time from 8 to 8:30 AM.Main Outcome Measures: Sleep patterns and behavior, daytime sleepiness, mood, data from the Health Cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
337
4
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(367 citation statements)
references
References 34 publications
25
337
4
1
Order By: Relevance
“…In fact, while this article and Special Issue were being prepared, the American Academy of Pediatrics released a policy statement recommending that middle and high schools delay the start of class to 8:30 a.m. or later (American Academy of Pediatrics 2014). A sizeable body of research finds earlier school start times to be associated with adolescents obtaining less sleep, exhibiting increased daytime sleepiness, and being more frequently tardy to school (Carrell et al 2011;Carskadon et al 1998;Dexter et al 2003;Edwards 2012;Hansen et al 2005;Owens et al 2010;Wahlstrom et al 2014;Wolfson et al 2007;Zhou et al 2012). Lufi et al (2011) showed that middle school students showed improved attention and decreased impulsivity when school start time was delayed by 1 h. Owens et al (2010) also found that adolescents showed improved mood and greater motivation after a later school start time was implemented.…”
Section: School Start Timementioning
confidence: 99%
See 1 more Smart Citation
“…In fact, while this article and Special Issue were being prepared, the American Academy of Pediatrics released a policy statement recommending that middle and high schools delay the start of class to 8:30 a.m. or later (American Academy of Pediatrics 2014). A sizeable body of research finds earlier school start times to be associated with adolescents obtaining less sleep, exhibiting increased daytime sleepiness, and being more frequently tardy to school (Carrell et al 2011;Carskadon et al 1998;Dexter et al 2003;Edwards 2012;Hansen et al 2005;Owens et al 2010;Wahlstrom et al 2014;Wolfson et al 2007;Zhou et al 2012). Lufi et al (2011) showed that middle school students showed improved attention and decreased impulsivity when school start time was delayed by 1 h. Owens et al (2010) also found that adolescents showed improved mood and greater motivation after a later school start time was implemented.…”
Section: School Start Timementioning
confidence: 99%
“…A sizeable body of research finds earlier school start times to be associated with adolescents obtaining less sleep, exhibiting increased daytime sleepiness, and being more frequently tardy to school (Carrell et al 2011;Carskadon et al 1998;Dexter et al 2003;Edwards 2012;Hansen et al 2005;Owens et al 2010;Wahlstrom et al 2014;Wolfson et al 2007;Zhou et al 2012). Lufi et al (2011) showed that middle school students showed improved attention and decreased impulsivity when school start time was delayed by 1 h. Owens et al (2010) also found that adolescents showed improved mood and greater motivation after a later school start time was implemented. Similarly, Wahlstrom et al (2014) recently found in a longitudinal, multi-site study in the US, that a school start time of 8:35 a.m. or later was associated with adolescents obtaining better grades as well as performing better on state and national achievement tests.…”
Section: School Start Timementioning
confidence: 99%
“…Starting school later 25 is a relatively easy implementation that could enhance learning, but is unpopular among parents, who need to go to work around the same time school starts. Rather than asking students to refrain from sleeping at school or to arrive later, naps could be explicitly employed as educational tools.…”
Section: R E V I E Wmentioning
confidence: 99%
“…Indeed, altered sleep patterns and sleep loss during adolescence have been associated with decrements in cognitive functioning, mood regulation and academic performance . Delaying school start times by as little as 30 minutes has been shown to have beneficial effects on alertness, mood, and general health (Owens et al 2010). …”
mentioning
confidence: 99%